Impact of COVID-19 on Asian economies and policy responses - Agarwal, Sumit 1970-; He, Zhiguo 1977-; Yeung, Bernard 1953- (World Scientific, 2020)
"On March 12th 2020, World Health Organization (WHO) declared the spreading of the new virus, 2019-nCoV, a pandemic. In Asia, the virus, more commonly referred to as COVID-19, has been spreading since the end of December. To contain the public health threat, almost all countries enforced a variety of measures, including lockdowns, to minimize face-to-face human interactions between the infected and the susceptible. While these vigilant measures save lives, they also generate a substantial negative economic shock that immediately halts demand and significantly disrupts supply, global production value chain and trade. The consequences are dire - considerable decline in output, massive surge in unemployment, countless bankruptcy cases, and unrelentless worries over financial stability. The result, a worldwide economic setback, is more severe than that experienced during the Great Financial Crisis of 2008-2009. Asia's experiences with COVID-19 precede that in the West. This fortuitous timing allows Asia to share its learnings drawn from experiences to benefit the world. The ABFER's community has gathered a collection of insights to inform the public. Besides providing access to research on the pandemic conducted in Asia, these commentaries offer comprehensive information on the effects of the pandemic, the effectiveness of measures employed to contain it and the subsequent economic impacts from such implementation. With granular analyses of government policies and their associated economic rescue packages, these commentaries elucidate the hard trade-offs between public health protection and economic security. Finally, the commentaries address the broader impact of the pandemic on international trade, global value chains and society."
Keywords: Pandemie; Schock -- Wirtschaft; Wirtschaftspolitik; COVID-19; Wirtschaft; Asien; COVID-19 (Disease) / Economic aspects / Asia; Asia / Economic conditions / 21st century; Asia / Economic policy / 21st century; Aufsatzsammlung